Features of Resilience in Psychology Students Depending on the Year of Study - Petrosyants V.R (Moscow State University of Psychology and Education, 2018)
The paper presents outcomes of an empirical research on the features of resilience and its components in psychology students and its relation with the year of study. We assumed that, considering the specifics of the chosen profession, resilience in the psychology students would increase from the first year to the fourth. The research involved 67 students of 1-4 years with an average age of 19,72 years. The data of the resilience test revealed the following: the second-year students displayed higher rates of general resilience as compared to the students of other years; the first-year students showed the lowest rates of resilience in the sample. The outcomes of our research may be used in the design of programmes of social psychological support for university students.